Determinants of Hospital Pharmacists' Job Satisfaction in Romanian Hospitals - Magdalena Iorga; Corina Dondaș; Camelia Soponaru; Ioan Antofie (MDPI AG, 2017)
Aim: The purpose of this study is to identify the level of job satisfaction among hospital pharmacists in Romania in relation to environmental, socio-demographic, and individual factors. Material and Methods: Seventy-eight hospital pharmacists were included in the research. The Job Satisfaction Scale was used to measure the level of satisfaction with their current jobs, and the TAS-20 was used to evaluate emotional experience and awareness. Additionally, 12 items were formulated in order to identify the reasons for dissatisfaction with jobs, such as budget, number of working hours, legislation, relationships with colleagues, hospital departments, or stakeholders. Data were analyzed using IBM SPSS Statistics version 23. Results: The analyses of the data revealed a low level of satisfaction regarding the pay-promotion subscale, a high level of satisfaction with the management-interpersonal relationship dimension, and a high level of satisfaction regarding the organization-communication subscale. Seventy-four percent of subjects are dissatisfied about the annual budget, and 86.3% are not at all satisfied with present legislation. Conclusions: These results are important for hospital pharmacists and hospital management in order to focus on health policies, management, and environmental issues, with the purpose of increasing the level of satisfaction among hospital pharmacists.